Effect of Bariatric Surgery on Hypertension: A Meta-analysis. (June 2014) - Wilhelm, Sheila M.; Young, Jamie; Kale-Pradhan, Pramodini B.
Purpose: Obesity is a growing epidemic leading to worldwide public health concerns. Bariatric surgery is an option for patients with a body mass index (BMI) >40 kg/m 2 or BMI of >35 kg/m 2 with serious comorbid conditions. This meta-analysis examines the effect of bariatric surgery on the improvement or resolution of hypertension.Methods: Two independent investigators conducted a literature search of PubMed (1990-2013) and Cochrane databases using the terms bariatric surgery and hypertension to identify appropriate human adult studies published in English. Studies were included if they reported the number of patients with hypertension prior to undergoing any bariatric surgery procedure and whether the hypertension improved or resolved postsurgery. The number of patients with hypertension and their response rates were extracted and analyzed using RevMan 5.2.5.Results: In all, 31 prospective and 26 retrospective studies met all criteria. The types of bariatric surgery performed included Roux-en-Y, gastric banding, laparoscopic adjustable gastric banding, vertical gastric banding, sleeve gastrectomy, duodenal switch, and biliopancreatic diversion. The time to first follow-up after surgery varied from 1 week to 7 years. Of the 57 studies, 32 reported improvement of hypertension in 32 628 of 51 241 patients (odds ratio [OR] = 13.24; 95% CI = 7.73, 22.68; P < 0.00001); 46 studies reported the resolution of hypertension in 24 902 of 49 844 patients (OR = 1.70; 95% CI = 1.13, 2.58; P = 0.01). A random-effects model was used because the heterogeneity between the studies was high ( I 2 = 97%).Conclusion: The results of this meta-analysis indicate that patients who undergo bariatric surgery experience improvement and resolution of their hypertension.